(NmATEMATI^ESKOE MODELIROWANIE ZADA^ DINAMIKI IZLU^A@]EGO GAZA (B/s - (N~ETWERU[KIN(B, (NbORIS nIKOLAEWI^s ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NFIZ(B.-(NMAT(B. (NLIT(B.,s, 1985)
(NbIBLIOGR(B.: (NS(B. 290-304 (229 (NNAZW(B.)s
Keywords: (NfIZIKAs